Towards comprehension of the surface state properties in the intrinsic magnetic topological insulators - Menshov, V. N. (Physical Review B)
Presently, the unusual quantum phenomena recently discovered in intrinsic antiferromagnetic topological insulators are far from being fully understood. Motivated by recent controversial ARPES results on the MnBi2Te4 family compounds, we theoretically study the underlying physics of spectral properties of such materials. By using a continual model, we address the issue of the topological surface fermions which simultaneously experience an exchange field of a regular antiferromagnetic alignment and a surface electrostatic potential. The emergent net exchange field acting on the surface state is shown to depend on the surface potential strength, of which variation could be associated with concentration fluctuations of antisite and other defects that are inevitably present in MnBi2Te4 material. In this scenario, we discuss the possible microscopic mechanism for change of both size and sign of the surface exchange gap from sample to sample. Furthermore, we provide a natural explanation for the appearance of a finite density of states inside the exchange gap in the case of strong fluctuations in the surface potential. Thus, our results allow for a unified interpretation of various spectroscopic measurements on intrinsic antiferromagnetic topological insulators. © 2022 American Physical Society.